2018
DOI: 10.2478/cer-2018-0031
|View full text |Cite
|
Sign up to set email alerts
|

Preconditions for the Tax Environment of a Alterglobal Development

Abstract: In this article, we analyzed economic surroundings as a precondition for the development of the tax environment in the context of alterglobal development. We admitted that economic globalization is harmful to the environment because it depends on its own viability: the constant increase in commodity consumption, the increased use of resources and the growing disposition to pollute waste in the ocean, on the ground, and in the air. So, we proposed considering and analyzing alterglobalization as a proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Such regulators are used by tax systems of OECD member countries. The principle of environmental regulation "polluter pays" became the basis of the environmental policy of the former Soviet States [5].…”
Section: Resultsmentioning
confidence: 99%
“…Such regulators are used by tax systems of OECD member countries. The principle of environmental regulation "polluter pays" became the basis of the environmental policy of the former Soviet States [5].…”
Section: Resultsmentioning
confidence: 99%
“…Building facilities for providing better sources of drinking water, managing wastewater, and reducing pollution is essential in this area. (Krysovatyy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The authors of work [4] took solid waste as the main research object, and they divided the waste into six categories, namely wood, plastic, waste paper, food, textile and rubber. However, through the experiment, it was found that vatyy, [9][10][11] and other scholars, in terms of how to overcome the global waste in global circulation chain, the development of the circular economy globalization, inclusive circulation economy analysis research on the impact of globalization, the economic environment as the prerequisite of the development of international development under the background of the tax environment, increase the green taxes and subsidies to phase out harmful to the environment, and fiscal incentives, VAT reductions and tax relief measures to provide the perfect conditions for the transition to a circular economy [11; 12]. Thus, promoting a circular economy in the context of the formation of circular electronic chains as a solution to overcome global waste.…”
Section: Literature Reviewmentioning
confidence: 98%